Her desire: a post-colonial reading of Rabindranath, Rokeya, and Bibhuti - Shuchi, Mahatajin Rumana (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2022.